Gaya Bahasa Lirik Lagu dalam Album Jadi Aku Sebentar Saja - Hartini, Sri; Kasnadi, Kasnadi; Astuti, Cutiana Windri (STKIP PGRI Ponorogo Press, 2021)
Poetry is the literary work that highlights the beauty of language. In everyday life, poetry is often found in song lyrics, which have a distincive and beautiful language style, for example the song album title Jadi Aku Sebentar Saja, popularized by Judika. The aims of the research are to descri be the figurative language in song lyrics and to find out their function. The research belongs to descriptive qualitative and designed as library research. The object of study which becomes the material of study is the song lyrics. From the results of the researcher’s data, it is known the description of language style contained in the Judika’s song album includes: (a) anaphora (b) epipora, (c) repetition, (d) alliterative (e) assonance, (f) polisidenton, (g) litotes, (h) hyperbole, (i) allegory, (k) metaphorical, (l) personification, (m) simile, (n) cynicism, (o) climax, and (p) irony. In addition, there is a stylistic functions of these figures. The function of language style is to enable song lyrics writer’s express his/her feelings about something that has been experienced, seen, or heard. Suggestions for readers when analyzing literary works of language style should be carried out more thoroughly and focus on the study in order to get maximum results.